Efficacy of Experimental Mouth Rinses on Caries-Related Biofilms in vitro - Steiger, Josiana; Braissant, Olivier; Waltimo, Tuomas; Astasov-Frauenhoffer, Monika (Frontiers in Oral Health, 2021)
This study assesses the efficacy of tin and PEG-3 tallow aminopropylamine in different concentrations on Streptococcus mutans biofilms to establish a new screening process for different antimicrobial agents and to gain more information on the antibacterial effects of these agents on cariogenic biofilms. Isothermal microcalorimetry was used to determine differences in two growth parameters: lag time and growth rate; additionally, reduction of active biofilms was calculated. Experimental mouth rinses with 400 ppm and 800 ppm tin derived from SnF2 revealed similar results (43.4% and 49.9% active biofilm reduction, respectively) to meridol mouth rinse (400 ppm tin combined with 1567 ppm PEG-3 tallow aminopropylamine; 55.3% active biofilm reduction) (p > 0.05), while no growth of S. mutans biofilms was detected during 72h for samples treated with an experimental rinse containing 1600 ppm tin (100% active biofilm reduction). Only the highest concentration (12536 ppm) of rinses containing PEG-3 tallow aminopropylamine derived from amine fluoride revealed comparable results to meridol (57.5% reduction of active biofilm). Lower concentrations of PEG-3 tallow aminopropylamine showed reductions of 16.9% for 3134 ppm and 33.5% for 6268 ppm. Maximum growth rate was significantly lower for all the samples containing SnF2 than for the control biofilms (p < 0.05); no differences were found between the control and all the PEG-3 tallow aminopropylamine (p > 0.05). The growth parameters show high reproducibility rates within the treated groups of biofilms as well as for the controls; thus, the screening method is providing reliable results.